ANALYSIS OF FACTORS INFLUENCING SURGICAL SITE INFECTION IN ABDOMINAL SURGERY: PREVENTIVE MEASURES AND CLINICAL OUTCOMES : Surgical Site Infection in Abdominal Surgery - MS. MONALISA PANDA; MS SAYANI SARKAR; MR. PRATYUSH CHAKRABORTY; MS. SULTANA KHATUN; DR. TANMAY ACHARIA; MS. SOVANA SAHOO (The Bioscan, 2026)
Surgical site infections (SSIs) remain one of the most common postoperative complications following abdominal surgery and are associated with increased morbidity, mortality, prolonged hospital stays, and healthcare expenditure. The present descriptive observational study was conducted to evaluate the factors influencing SSIs in abdominal surgery and to identify effective preventive and therapeutic measures. The study was carried out over a one-year period at Tamralipto Government Medical College and Hospital and included 30 patients aged between 15 and 60 years who developed SSIs following abdominal surgical procedures. Data were collected from patient records, clinical observations, and postoperative follow-up. Demographic variables, surgical procedures, wound characteristics, causative factors, symptoms, dressing intervals, antibiotic therapy, and wound healing duration were analyzed. Female patients constituted 66.6% of cases, while males represented 33.4%. Gastrointestinal surgeries and secondary suturing after caesarean section accounted for the majority of SSI cases. Major contributing factors included microbial contamination, low immunity, hypertension, diabetes mellitus, emergency surgery, poor tissue handling, prolonged hospital stay, and improper wound care. The study observed that appropriate antibiotic therapy, proper sterilization, regular dressing, negative-pressure wound therapy, and suitable suturing techniques significantly improved wound healing outcomes. The findings emphasize the importance of perioperative sterility, rational antibiotic use, and evidence-based wound management in reducing SSI incidence. Implementation of effective preventive strategies and improved postoperative care may substantially reduce complications and improve patient outcomes following abdominal surgery.